Criterio previsor para la selección de pares en redes P2P móviles - Meseguer-Rojas, Andrés (Instituto Tecnológico de Costa Rica., 2015)
The traditional telephony structure, with towers centralizyng the communication is offering a service unable to match the ongrowing demand. P2P approaches have probe progress towards a solution. However, the devices's mobility represents a challenge where their migration pattern is diffcult to predict and is determined by the will of living beans.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2015.
Keywords: P2P; Telefonía móvil; Criterio previsor; Movilidad